Alat Ukur Kadar Gula Darah dan Informasi Dosis Insulin Berbasis Sinyal Photopletysmograph (PPG) - Putri Madona; Erwin Saputra; Hendri Novia Syamsir (Teknik Informatika, 2018)
Glucose and corresponding required insulin dosage measurement based on Photoplethysmograph (PPG), is a non-invasive method. The PPG equipment is able to calculate the insulin dosage based on BMI (Body Mass Index) information. The resulted PPG Signal will be transferred into microcontroller to be examined and converted into glucose index and insulin dosage displayed on the LCD screen. Taken 15 respondent to be examined with 20 up to 50 range of ages. The resulted measurements are compared with the one resulted by conventional measurement method. Based on the analysis, the proposed method is able to examine the glucose and insulin dosage up to 80% of accuracy in average.